Anti-oxidant protective effects of Cassia alata in rats exposed to carbon tetrachloride - MO Wegwu; EO Ayalogu; OJ Sule (Journal of Applied Sciences and Environmental Management, 2006)
The protective activity of Cassia alata against carbon tetrachloride (CCl4) – induced hepatotoxicity in rats was assessed. Crude extracts of petals of the plant in 0.5% ethanol were administered by intubation for 14 days prior to injection of 0.5ml Kg-1 CCl4 into the rats. Serum aspartate aminotransferase and alanine aminotransferase levels, 18 hours after CCl4 administration, decreased significantly (P < 0.05) in rats treated with the extracts than in CCl4 – treated rats only. These findings suggest that Cassia alata may be protective against hepatotoxin-induced liver damage in rats. Journal of Applied Sciences and Environmental Management Vol. 9(3) 2005: 77-80